Ethylene production from ethanol dehydration over mesoporous SBA-15 catalyst derived from palm oil clinker waste - Cheng, Y.W. (Elsevier Ltd, 2020)
The silica-rich palm oil clinker (POC) from oil palm agroindustry is often dumped in landfill. This work investigated the valorisation of POC into Santa Barbara Amorphous-15 (SBA-15) catalyst, the modulation of its surface acidity, and its application in dehydration of ethanol to ethylene. With commercial SBA-15 SBA-15(Comm.) as reference, the successful fabrication of POC-derived SBA-15 POC-SBA-15(pH = 3, 5, and 7) were validated by spectroscopic and microscopic characterisation. From the results of temperature-programmed desorption of ammonia, the SBA-15(Comm.) have high strong acidity while POC-SBA-15 exhibit enriched weak-moderate acidity. For ethanol dehydration over SBA-15 at 200â400 Â°C, the ethanol conversion (XC2H5OH) and ethylene selectivity (SC2H4) rise with temperature. The catalytic activity was ranked as SBA-15(Comm.) < POC-SBA-15(3) < POC-SBA-15(7) < POC-SBA-15(5). Spent catalysts characterisation unanimously confirms the least carbon deposition on POC-SBA-15(5), which subsequently used to study the effect of initial ethanol concentration and liquid hourly space velocity (LHSV). When 99.5 wt% ethanol diluted to 50 wt%, the competitive adsorption between ethanol and water reduces XC2H5OH but enhances SC2H4. Further ethanol dilution (â¤30 wt%) deteriorates SC2H4 following remarkable ethanol steam reforming at elevated temperature (â¥350 Â°C). For 50 wt% ethanol dehydration over POC-SBA-15(5) at 400 Â°C, a greater LHSV furnishes a higher ethanol partial pressure that increases XC2H5OH but decreases SC2H4. When LHSV >16 mL/gÂ·h, the saturation of finite active sites with adsorbates renders the drastic declination of XC2H5OH and SC2H4. For ethanol dehydration over POC-SBA-15(5), the optimal conditions are temperature of 400 Â°C, initial ethanol concentration of 50 wt%, and LHSV of 16 mL/gÂ·h. Fresh POC-SBA-15(5) steadily catalyses the optimal process (73.33% XC2H5OH and 84.70% SC2H4) up to 105 h. Meanwhile, regenerated POC-SBA-15(5) achieves a lower catalytic activity (71.95% XC2H5OH and 81.96% SC2H4). Â© 2019 Elsevier Ltd